2011
DOI: 10.1177/1077546310382808
|View full text |Cite
|
Sign up to set email alerts
|

Transient responses of Timoshenko beams subject to a moving mass

Abstract: The dynamic behavior of beam structures subject to a moving mass is a topic of practical importance in many research fields. In this study, the method of reverberation-ray matrix is presented to investigate the dynamic responses of an undamped Timoshenko beam subject to a moving mass. Based on Inglis’s assumption, the moving mass is simplified into a moving force and a concentrated mass fixed at the mid-span of the beam. Two dual local coordinates are introduced. Based on the theory of elastodynamics, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…A number of researches have been carried out on the design of vehicle/track systems [1][2][3][4][5][6][7][8][9]. Researchers have been mainly giving attention on the wheel-bogie system and overall vehicle system characteristics, so they regard axle box bearings and wheelsets as a whole [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researches have been carried out on the design of vehicle/track systems [1][2][3][4][5][6][7][8][9]. Researchers have been mainly giving attention on the wheel-bogie system and overall vehicle system characteristics, so they regard axle box bearings and wheelsets as a whole [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MRRM has been directed towards the study of functionally graded or laminated structures (Zhou et al, 2009;Li et al, 2012;Liu et al, 2013;Miao et al, 2013;2015). It is aimed to obtain a unidirectional traveling wave form solution for OCCSs, which is of good consistency with the solutions for beams and plates presented in (Yu, 2007a;2007b;Jiang, 2011;Liu et al, 2010;2011a). Therefore, the formulation presented in this paper should prove to be fundamental for vibration analysis of ring-stiffened OCCSs and plate-shell coupled structures.…”
Section: Introductionmentioning
confidence: 91%
“…that allow the coefficients C 0 , D 0 to be completely calculated with expressions (20). Thus, the frequency response (25), (26) is fully determined for the given discretely moving load.…”
Section: Frequency Response Of Cracked Beam To General Moving Loadmentioning
confidence: 99%
“…Moreover, both the methods are poorly applicable for evaluating the shear force [18] and high frequency components [19]. Jiang et al have demonstrated in [20,21] that the moving load problem can be investigated straightforwardly in the frequency domain. Khiem et al [22] have proposed a spectral approach to the moving load problem that is solved completely in frequency domain.…”
Section: Introductionmentioning
confidence: 99%